2007
DOI: 10.1148/radiol.2451061502
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer: Accurate Determination of Extracapsular Extension with High-Spatial-Resolution Dynamic Contrast-enhanced and T2-weighted MR Imaging—Initial Results

Abstract: The combination of high-spatial-resolution dynamic contrast-enhanced MR imaging and T2-weighted MR imaging yields improved assessment of ECE and better results for prostate cancer staging compared with either technique independently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(130 citation statements)
references
References 53 publications
2
121
0
7
Order By: Relevance
“…The incorporation of other MR techniques, such as dynamic perfusion or diffusion-weighted imaging, can further improve the performance of MR examinations in the detection and staging of prostate cancer (36)(37)(38)(39). It would be of clinical interest in the future to investigate whether multiparametric examinations in which all of these state-of-the-art techniques are combined can yield superior diagnostic information for stratifying patients with clinical stage T1c prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of other MR techniques, such as dynamic perfusion or diffusion-weighted imaging, can further improve the performance of MR examinations in the detection and staging of prostate cancer (36)(37)(38)(39). It would be of clinical interest in the future to investigate whether multiparametric examinations in which all of these state-of-the-art techniques are combined can yield superior diagnostic information for stratifying patients with clinical stage T1c prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Adding functional parameters to T2WI may improve this. One study reported that adding DCEI to T2WI for T-staging resulted in a sensitivity of 86% and specificity of 95% for detecting EPE [112]. Another study failed to validate these findings [113], however, and two studies reported that combining MRS and T2WI failed to improve accuracy over T2WI alone in staging [114,115].…”
Section: Mri In T-staging Treatment Selection and Planningmentioning
confidence: 99%
“…The incremental value of high spatial resolution DCE MRI was shown recently [77]. This imaging strategy acquires higher-resolution images with smaller voxel sizes than has been possible with prior MR technology and more comprehensive tissue sampling compared to other pre-surgical assessments.…”
Section: Mri Of the Prostate At Beth Israel Deaconess Medical Center mentioning
confidence: 99%